Decentralized Exchange - Malamud, Semyon; Rostek, Marzena (American Economic Review, 2017)
Most assets are traded in multiple interconnected trading venues. This paper develops an equilibrium model of decentralized markets that accommodates general market structures with coexisting exchanges. Decentralized markets can allocate risk among traders with different risk preferences more efficiently, thus realizing gains from trade that cannot be reproduced in centralized markets. Market decentralization always increases price impact. Yet, markets in which assets are traded in multiple exchanges, whether they are disjoint or intermediated, can give higher welfare than the centralized market with the same traders and assets. In decentralized markets, demand substitutability across assets is endogenous and heterogeneous among traders. (JEL D43, D44, D85, G11, G12)